2019
DOI: 10.3390/su11164270
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Environmental System Knowledge in Promoting University Students’ Environmental Attitudes and Pro-Environmental Behaviors

Abstract: This study aims to investigate the role of environmental system knowledge in promoting pro-environmental behaviors. Relationships between environmental knowledge and environmental attitudes as well as environmental knowledge and pro-environmental behaviors were analyzed. Environmental system knowledge includes knowledge of political ecology, sustainable development, environment and ecology, and environmental situations. This study included 128 students enrolling in the elective course entitled “Environment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 64 publications
5
78
1
3
Order By: Relevance
“…The effect of EME on PEB has been widely studied across the world. The relationship is diverse depending on the region, religion, culture and many other factors [ 6 , 24 ]. Most of the studies found a positive relationship between EME and PEB; however, still, some studies suggested that a high level of environmental education will not necessarily reflect environmental friendly behaviour [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of EME on PEB has been widely studied across the world. The relationship is diverse depending on the region, religion, culture and many other factors [ 6 , 24 ]. Most of the studies found a positive relationship between EME and PEB; however, still, some studies suggested that a high level of environmental education will not necessarily reflect environmental friendly behaviour [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Highly educated (those perusing or who graduated from bachelor’s degree programs are considered as educated persons, whereas those enrolled or graduated from master’s or higher degree programs are considered as highly educated persons) persons are more motivated to bettering the environment, because education produces awareness about the potential damage to the environment [ 3 , 4 ]. Mostly, education provides a high level of knowledge and awareness about environmental problems and its solutions which results in sustainable and pro-environmental behaviour (PEB) [ 5 , 6 ]. It is believed that, currently, human behaviour has detrimental impacts on the environment, and, especially, younger generations will be affected more owing to the current global environmental problems which will continue to become worse in the future if not well addressed [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate change is of utmost importance to modern society [1][2][3][4][5][6][7], and pro-environmental behavior, including climate-friendly actions, can be regarded as an efficient approach to address this challenge [8][9][10][11][12][13]. This behavior can be demonstrated by the general public [14][15][16][17][18], selected groups such as students [19][20][21][22][23], decision-makers [24][25][26][27], and business leaders [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The attention paid to climate change will lead to increased interest in the coming years, so universities must engage in the development of more specialized curricula [29][30][31]. There is an urgent need to create multidisciplinary teams in building decision-making that understand the impact of climate on cities [32].…”
Section: Introductionmentioning
confidence: 99%